PROYECTO DE INVERSIÓN PARA LA IMPLEMENTACIÓN DE UNA HOSTERÍA ECO-TURÍSTICA EN LA PARROQUIA CASACAY, CANTÓN PASAJE, PROVINCIA DE EL ORO, AÑO 2014 - Romero Cuenca, Julio Stalin (2015)
In the parish Casacay there is a low tourism development due to the lack of adequate infrastructure to promote greater number of tourists to take advantage of the tourism potential that has therefore to overcome this problem is proposed in this paper “Proyecto de inversión para la implementación de una Hostería Eco Turística en la parroquia Casacay, cantón Pasaje, provincia de El Oro, año 2014”. The general objective was: To promote tourism development in the canton Passage through the creation of an ecotourism lodge in the parish Casacay, in order to take advantage of its tourist wealth to turn them into income-generating sources. Participants included domestic and foreign tourists visiting tourist sites Pasaje city and people interested in undertaking projects of Casacay parish, a place which was conducted the investigation. The scientific method used in their ways: inductive, deductive, synthetic, analytical and statistical. The techniques applied were the literature and survey their instruments as bibliographic records and questionnaire survey. The project has an investment of $ 121.416.84 financed with a 67.06% equity and 32.94% on credit for four years with an interest rate of 10% by the Development Bank; for calculating financial indicators cash flow to 10 years where an NPV of $ 62,215.21, an IRR of 22.57% and a cost / benefit ratio of 1.25 was obtained it was constructed. It is concluded according to the given conditions of the study, that the project is feasible so its implementation is recommended as it responds to the problems of the place, inserting in the development axes established in the Plan de Ordenamiento Territorial of the Casacay parish, and in the objectives of Buen Vivir. Keywords: design, eco-tourism, hosteria, feasibility.